Role of SpoVG in Asymmetric Septation in Bacillus subtilis - Matsuno, Kiyoshi (American Society for Microbiology, 1999)
Deletion of the citC gene, coding for isocitrate dehydrogenase, arrests sporulation of Bacillus subtilis at stage I after bipolar localization of the cell division protein FtsZ but before formation of the asymmetric septum. A spontaneous extragenic suppressor mutation that overcame the stage I block was found to map within the spoVG gene. The suppressing mutation and other spoVG loss-of-function mutations enabled citC mutant cells to form asymmetric septa and to activate the forespore-specific sigma factor ς(F). However, little induction of mother cell-specific, ς(E)-dependent sporulation genes was observed in a citC spoVG double mutant, indicating that there is an additional defect(s) in compartmentalized gene expression in the citC mutant. These other defects could be partially overcome by reducing the synthesis of citrate, by buffering the medium, or by adding excess MnCl(2). Overexpression of the spoVG gene in wild-type cells significantly delayed ς(F) activation. Increased expression and stability of SpoVG in citC mutant cells may contribute to the citC mutant phenotype. Inactivation of the spoVG gene caused a population of otherwise wild-type cells to produce a small number of minicells during growth and caused sporulating cells to complete asymmetric septation more rapidly than normal. Unlike the case for inactivation of the cell division inhibitor gene minD, many of these minicells contained DNA and appeared only when the primary sporulation signal transduction pathway, the Spo0A phosphorelay, was active. These results suggest that SpoVG interferes with or is a negative regulator of the pathway leading to asymmetric septation.